Cryogenic thermal absorptance measurements on small-diameter stainless steel tubing. (March 2016) - Tuttle, James; Jahromi, Amir; Canavan, Edgar; DiPirro, Michael
Highlights: The James Webb Space Telescope includes a mechanical cryocooler. We measured the thermal absorptance of this cooler's gold-plated helium gas lines. We measured heat absorbed by a cooler line sample in a blackbody cavity. The tubing has a higher absorptance than would be expected for smooth bulk gold. Abstract: The Mid Infrared Instrument (MIRI) on the James Webb Space Telescope includes a mechanical cryocooler which cools its detectors to their 6 K operating temperature. The coolant gas flows through several meters of small-diameter stainless steel tubing, which is exposed to thermal radiation from its environment. Over much of its length this tubing is gold-plated to minimize the absorption of this radiant heat. In order to confirm that the cryocooler will meet MIRI's requirements, the thermal absorptance of this tubing was measured as a function of its environment temperature. We describe the measurement technique and present the results.